The Violation of Cooperative Principle in Conversational of Presidential Debate Indonesia 2019 - Rossy Halimatun Rosyidah (Masters in English Education, The Directory of Postgraduate Program,Universitas Muhammadiyah Malang, 2020)
Politician will use various style of political languages to influence and convince people to achieve a victory in campaign. Indonesia has conducted debate as a form of campaign in the presidential election. Therefore, violating the cooperative principle in political language often occurs. The researcher conducts this research to know how does the President and Vice President candidates violate cooperative principle, especially in quality and relevance maxim, to know what is the function of the violation, and to know what is the meaning of violation. The method of this research is descriptive qualitative. The subject of this research is the dialogue of President and Vice President candidate in debate. The object of this research is violation of maxim quality and relevance. The instrument of this research is the table indicator. The data obtained from the utterances of President and Vice President candidate. the researcher analyzed the data by using literature study, document study, and content analysis. Then, the validity of data used triangulation method. The result of this study is the President and Vice President candidate number 01 violated maxim relevance and maxim quality. The function of violation are; commisive and assertive. The meaning of the utterances is promising and giving an opinion. Then, the candidate number 02 violated maxim quality with assertive function. The meaning of the utterances is boasting.